2022
DOI: 10.1111/eve.13659
|View full text |Cite
|
Sign up to set email alerts
|

Low‐field MRI findings and follow‐up of central tarsal bone fractures in four non‐racehorses

Abstract: Background: Central tarsal bone fractures in non-racehorses are uncommon and their MRI appearance and follow-up have not been described. Objectives:To describe the clinical and MRI characteristics and follow-up of central tarsal bone fractures in non-racehorses. Study design:Retrospective descriptive case series. Methods:The low-field MRI appearance of central tarsal bone fractures in sports horses identified over a 9-year period, was reviewed. Follow-up MRI examinations, treatment and clinical outcome were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 22 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Despite problems with screw placement due to CTB curvature, clinical experience at this institution and in published literature 2,4,6,9 has shown that these fractures heal well with internal fixation. CTB fractures are unique in that screw placement often requires the violation of several basic principles of internal fixation that are considered clinically acceptable in these cases.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Despite problems with screw placement due to CTB curvature, clinical experience at this institution and in published literature 2,4,6,9 has shown that these fractures heal well with internal fixation. CTB fractures are unique in that screw placement often requires the violation of several basic principles of internal fixation that are considered clinically acceptable in these cases.…”
Section: Discussionmentioning
confidence: 85%
“…Also, in most fractures the drill tract should be continued through the far cortex to achieve maximal screw purchase and compression of the fracture fragment 14 ; however, the ideal amount of bone engagement beyond the fracture is unknown for CTB fractures. Compared to other fracture locations in horses, it is likely that less of the screw needs to extend beyond the fracture due to the degree of sclerosis that is often present 4–6 . Small tarsal bone fractures are also provided additional stability by a tight fibrous joint capsule and the surrounding tendons and ligaments in the distal tarsus 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations